2018
DOI: 10.1007/s12639-018-0984-0
|View full text |Cite
|
Sign up to set email alerts
|

Genistein: is the multifarious botanical a natural anthelmintic too?

Abstract: Genistein (4',5,7-trihydroxyisoflavone) is naturally present in plants of the soy family and is known to have various pharmacological activities, such as anti-cancer, anti-diabetic, anti-oxidant, etc. The phytoestrogen is one of the major isoflavones found in some medicinal plants having anthelmintic properties. This review describes the putative role of genistein as an anthelmintic, which has been tested on some helminth parasites in vitro. Genistein has been shown to cause paralysis and alterations in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 117 publications
0
18
0
Order By: Relevance
“…Egg output and development were positively correlated in a moderate level. The nematocidal effects of Genistein against helminth parasite and cestodes were already confirmed (Tandon and Das, 2018), as well as the embryonic and larval lethality of Flavone against C. elegans (Yong-Uk et al, 2008). Due to the low number of studies on Hydrolysable tannin, we decided to include Gallic and Tannic acid among our assays.…”
Section: Discussionmentioning
confidence: 93%
“…Egg output and development were positively correlated in a moderate level. The nematocidal effects of Genistein against helminth parasite and cestodes were already confirmed (Tandon and Das, 2018), as well as the embryonic and larval lethality of Flavone against C. elegans (Yong-Uk et al, 2008). Due to the low number of studies on Hydrolysable tannin, we decided to include Gallic and Tannic acid among our assays.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have also demonstrated that isoflavone inhibited or slowed the motility of Heterodera zeae, Meloidogyne javanica and Meloidogyne incognita juveniles (Faizi et al, 2011;Shaukat et al, 2003;Sommerville and Davey, 2002;Wuyts et al, 2006). Genistein and terpenoids have shown to cause paralysis and alterations in the tegument and tegumental enzymes of nematodes (Tandon and Das, 2018). Exposure to 0.5 mg mL -1 Genistein provided a pronounced reduction of the activity of non-specific esterases (NSE) and cholinesterase (ChE), which were found in close association with the central and peripheral nervous components (Maule et al, 1993).…”
Section: Discussionmentioning
confidence: 95%
“…Genistein (5, 7-dihydroxy-3-(4-hydroxyphenyl) chromen-4-one) is an isoflavanoid compound, naturally occurring in plants of the soy family, belonging to a group of nutraceuticals ( Tandon & Das, 2018 ) ( Fig. 3 ).…”
Section: The Effects Of Curcumin On Flatwormsmentioning
confidence: 99%
“…Rao and Reddy (1991) examined the plant’s active ingredients where genistein represented the major component in the ethanolic extract of plant root tuber peel, which was subsequently used for its isolation. According to many in vitro studies (see for review: Tandon & Das, 2018 ), genistein has been shown to affect several enzymatic systems, localized in the tegument and other worm´s compartments in various species of helminths, thus suggesting its multiple molecular targets.…”
Section: The Effects Of Curcumin On Flatwormsmentioning
confidence: 99%